Pengendalian Persediaan Pozzolan di PT Semen Padang - Prima Fithri; Annise Sindikia (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2014)
Inventory of raw materials is the most important thing to produce the product. Inventory control of the raw materials quantityalso refers to the production process at the factory. PT Semen Padang used raw materials including cement manufacture clay, limestone, silica, gypsum, pozzolan and sand iron or copper slag. Among the raw materials, the most used is pozzolan. This research will be carried out data processing for inventory control using the EOQ (Economic Order Quantity) and POQ (Periodic Order Quantity) to compare with inventory control has been implemented by the company. The data collected for this study include data processing is the use of historical data pozzolan material per period in 2012 and 2013, the cost of raw materials ordering pozzolan, pozzolan storage costs of raw materials and lead time, acceptance of pozzolan from suppliers to storage. Data processing is performed to determine the inventory control of raw materials sand pozzolan in 2014. The results and conclusions obtained are forecasting the use of pozzolan in 2014 is 1.135.355,77 tons it means will be more than in previous years and the inventory control with POQ (Periodic Order Quantity) produces the minimum inventory costs with price Rp 1.775.179.959,61.